SG-SP1 Suppresses Mast Cell-Mediated Allergic Inflammation via Inhibition of FcεRI Signaling - Kim, Min-Jong; Je, In-Gyu; Song, Jaeyoung; Fei, Xiang; Lee, Soyoung; Yang, Huiseon; Kang, Wonku; Jang, Yong Hyun; Seo, Seung-Yong; Kim, Sang-Hyun (Frontiers in Immunology, 2020)
Background: As the number of allergic disease increases, studies to identify new treatments take on new urgency. Epigallocatechin gallate (EGCG), a major component of green tea, has been shown to possess a wide range of pharmacological properties, including anti-inflammation and anti-viral infection. In previous study, gallic acid (GA), a part of EGCG, has shown anti-allergic inflammatory effect. To improve on preliminary evidence that GA has allergy mitigating effect, we designed SG-SP1 based on GA, and aimed to assess the effects of SG-SP1 on mast cell-mediated allergic inflammation using various animal and in vitro models. Methods: For in vitro experiments, various types of IgE-stimulated mast cells (RBL-2H3: mast cell-like basophilic leukemia cells, and primary cultured peritoneal and bone marrow-derived mast cells) were used to determine the role of SG-SP1 (0.1-1 nM). Immunoglobulin (Ig) E-induced passive cutaneous anaphylaxis and ovalbumin-induced systemic anaphylaxis, standard animal models for immediate-type hypersensitivity were also used. Results: For in vitro, SG-SP1 reduced degranulation of mast cells by down-regulating intracellular calcium levels in a concentration-dependent manner. SG-SP1 decreased expression and secretion of inflammatory cytokines in activated mast cells. This suppressive effect was associated with inhibition of the phosphorylation of Lyn, Syk and Akt, and the nuclear translocation of nuclear factor-κB. Due to the strong inhibitory effect of SG-SP1 on Lyn, the known upstream signaling to FcεRI-dependent pathway, we confirmed the direct binding of SG-SP1 to FcεRI, a high affinity IgE receptor by surface plasmon resonance experiment. Oral administration of SG-SP1 hindered allergic symptoms of both anaphylaxis models evidenced by reduction of hypothermia, serum IgE, ear thickness, and tissue pigmentation. This inhibition was mediated by the reductions in serum histamine and interleukin-4. Conclusions: We determined that SG-SP1 directly interacts with FcεRI and propose SG-SP1 as a therapeutic candidate for mast cell-mediated allergic inflammatory disorders via inhibition of FcεRI signaling.